RECONSIDERAREA MONITORIZĂRII DIN PERSPECTIVA CALITĂŢII EDUCAŢIEI - USM ADMIN (Studia Universitatis Moldaviae: Stiinte ale Educatiei, 2009)
The present article approaches the problem of the necessity of a modern view on education quality, monitoring in perspective a systemic and process approach.